The Cancer Epigenome: Its Origins, Contributions to Tumorigenesis, and Translational Implications - Baylin, Stephen B. (American Thoracic Society, 2012)
Epigenetic abnormalities in lung and other cancers continue to be defined at a rapid pace. We are coming to appreciate that cancers have an “epigenetic landscape” wherein genes vulnerable to abnormalities, such as promoter DNA hypermethylation and associated gene silencing, tend to reside in defined nuclear positions and chromosome domains and relationships to chromatin regulation, which facilitates states of stem cell renewal. These same genes and domains are also vulnerable to epigenetic abnormalities induced by factors to which cells are exposed during cancer risk states, such as chronic inflammation. We can use all of this basic information for translational purposes in terms of deriving biomarkers for cancer risk states and detection and therapeutic strategies.